Respostas
respondido por:
8
{ x + y = 9
{ - x + y = - 5
x = 9 - y
- x + y = - 5
- ( 9 - y ) + y = - 5
- 9 + y + y = - 5
y + y = - 5 + 9
2y = 4
y = 4/2
y = 2
x = 9 - y
x = 9 - ( 2 )
x = 9 - 2
x = 7
S = { 7 , 2 }.
Espero ter ajudado e bons estudos !!!
{ - x + y = - 5
x = 9 - y
- x + y = - 5
- ( 9 - y ) + y = - 5
- 9 + y + y = - 5
y + y = - 5 + 9
2y = 4
y = 4/2
y = 2
x = 9 - y
x = 9 - ( 2 )
x = 9 - 2
x = 7
S = { 7 , 2 }.
Espero ter ajudado e bons estudos !!!
alistonfeitosa:
De nada !!
respondido por:
5
x + y = 9
- x + y = 5
2y + 14 => y + 7
Se y = 7 => x = 2
- x + y = 5
2y + 14 => y + 7
Se y = 7 => x = 2
Perguntas similares
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
10 anos atrás